Acculturation of Architectural and Interior Elements in the Conversion of a Colonial Building into Cut Meutia Mosque, Central Jakarta - Fauzia Latif (Jurnal Desain Interior, 2025)
The Cut Meutia Mosque in Central Jakarta is a historical landmark that represents the conversion of a colonial-era building into a religious space. Originally constructed as an administrative office during the Dutch colonial period, the structure was later converted into a mosque while preserving its architectural integrity. This study examines the acculturation of colonial architectural features with Islamic interior elements, exploring how European design principles were integrated with religious and cultural needs. Using a qualitative case study approach, the research incorporates direct observation, interviews, and document analysis. Findings indicate that key structural elements, such as high ceilings, large windows, and classical columns, were maintained, while Islamic modifications, including the addition of a mihrab and Arabic calligraphy, enhanced its spiritual identity. This study highlights the significance of adaptive reuse in heritage conservation, demonstrating how historical buildings can retain their original character while accommodating new functions. By analyzing this conversion, the research provides insights into the broader discourse on architectural adaptation and the integration of Islamic identity in converted colonial structures. The findings contribute to discussions on heritage preservation in Indonesia, emphasizing the importance of maintaining historical buildings while addressing contemporary religious and cultural need.